E-LOCATION INDICATOR BASED ON INTRANET AS A SUPPORT OF LEARNING FLIGHT PLAN AT AVIATION POLYTECHNIC OF SURABAYA - Putri Firdha Rose, Salsabilah; Rochmawati, Laila; Hadi Rantelinggi, Parma; Aman, Syahrul; Maharani Sukma, Meita (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Location Indicator which is useful for knowing the name of the aerodrome and the location of the aerodrome.Website E-Location indicator based on Intranet using internal network. This research uses research and development methods. The development model in this study is 4-D from Thiagarajan with 4 stages, namely define, design, develop, disseminate. The population used was 2 material experts and 1 media expert and 23 cadets D-3 Aeronautical Communication batch 6 at Aviation Polytechnic of Surabaya. This research has been validated by material experts and media experts and has been declared fit for use. The results of this study show that 92.3% of respondents strongly agree with the E-Location indicator website and the remaining 7.7% did not carry out further research.